Diagnostic Value of Hematological Parameters in COVID-19 Patients - Syeda Bint-e-Zahra, Jawad Zaffar Choudry, Hamid Iqbal, Zill-E-Rubab, Mehreen Aftab Khan, Syed Tasadak Mehdi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Covid-19 was fulminant and had a rapid spread in China and many other areas around the globe. This is a life threatening problem at present as it causes the severe acute respiratory syndrome corona virus (SARS-CoV). Aim: To explore the diagnostic value of hematological parameters in COVID-19 patients. Study Design: Comparative Cross-Sectional Study. Methodology: Patients (n=200) having COVID-19 were enrolled. All patients had CBC and inflammatory markers. Various hematological markers were used as prognostic markers. SPSS software, v 23 analyzed data. Independent t-test and Chi square were applied and p value of <0.05 was taken significant. Results: Mean age for patients having COVID was 47± 15.48 years. Mean values of hematological parameters and platelet count were significantly low among COVID patients when compared with non-COVID patients thus having significant difference. Practical Implication: This study highlighted simple, cost-effective hematological parameters that can be useful diagnostic tools for COVI-19. This study indicated that routine tests can guide towards disease like COVID-19. Conclusion: We concluded that hematological parameters (TLC, ANC, AMC, NLR and platelet count) play a vital role as diagnostic tool for COVID-19 patients. Keywords: Covid-19, d-Dimers, NLR, NLM and Hematological Parameters.